Surface topography analysis of mg-based composites with different nanoparticle contents disintegrated using abrasive water jet - Mardi, K.B.; Dixit, A.R.; Pramanik, Alokesh; Hvizdos, P.; Mallick, A.; Nag, A.; Hloch, S. (MDPI, 2021)
This study investigated the effect of abrasive water jet kinematic parameters, such as jet traverse speed and water pressure, on the surface of magnesium-based metal matrix nanocomposites (Mg-MMNCs) reinforced with 50 nm (average particle size) Al2O3 particles at concentrations of 0.66 and 1.11 wt.%. The extent of grooving caused by abrasive particles and irregularities in the abrasive waterjet machined surface with respect to traverse speed (20, 40, 250 and 500 mm/min), abrasive flow rate (200 and 300 g/min) and water pressure (100 and 400 MPa) was investigated using surface topography measurements. The results helped to identify the mode of material disintegration during the process. The nanoindentation results show that material softening was decreased in nanocomposites with higher reinforcement content due to the presence of a sufficient amount of nanoparticles (1.11 wt.%), which protected the surface from damage. The values of selected surface roughness profile parameters—average roughness (Ra), maximum height of peak (Rp) and maximum depth of valleys (Rv)—reveal a comparatively smooth surface finish in composites reinforced with 1.11 wt.% at a traverse speed of 500 mm/min. Moreover, abrasive waterjet machining at high water pressure (400 MPa) produced better surface quality due to sufficient material removal and effective cleaning of debris from the machining zone as compared to a low water pressure (100 MPa), low traverse speed (5 mm/min) and low abrasive mass flow rate (200 g/min).